(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In an increasingly globalized world, the demand for a skilled workforce with strong English language proficiency is paramount, particularly within vocational sectors. This article explores the critical need for improving English literacy in professional skills among vocational education students. It outlines a multi-faceted approach, presenting concrete measures across curriculum development, pedagogical strategies, teacher training, resource provision, and assessment methods. By integrating English language learning with vocational training, institutions can equip graduates with the linguistic competence necessary to thrive in international job markets, access global technical knowledge, and contribute effectively to economic development.